2021
DOI: 10.1093/heapol/czaa157
|View full text |Cite
|
Sign up to set email alerts
|

Cost of scaling-up comprehensive primary health care in India: Implications for universal health coverage

Abstract: India has announced the ambitious program to transform the current primary healthcare facilities to health and wellness centres (HWCs) for provision of comprehensive primary health care (CPHC). We undertook this study to assess the cost of this scale-up to inform decisions on budgetary allocation, as well as to set the norms for capitation-based payments. The scale-up cost was assessed from both a financial and an economic perspective. Primary data on resources used to provide services in 93 sub-health centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The number of deaths averted were estimated to be highest with annual screening (1302 [923-1793] per 100 000 population), followed by screening every 3 years (619 [401-935] per 100 000 population), every 5 years (406 [255-626] per 100 000 population), and least with screening every 20 years (96 [57-151] per 100 000 population; table 1). Gains in life-years and QALYs are shown in table 1 and for alternative tests in the appendix (pp [29][30][31][32][33]. The number of complications and health outcomes estimated for population-based screening in the group aged between 45 and 65 years are shown in the appendix (pp [42][43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of deaths averted were estimated to be highest with annual screening (1302 [923-1793] per 100 000 population), followed by screening every 3 years (619 [401-935] per 100 000 population), every 5 years (406 [255-626] per 100 000 population), and least with screening every 20 years (96 [57-151] per 100 000 population; table 1). Gains in life-years and QALYs are shown in table 1 and for alternative tests in the appendix (pp [29][30][31][32][33]. The number of complications and health outcomes estimated for population-based screening in the group aged between 45 and 65 years are shown in the appendix (pp [42][43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…The details for the cost of services at the HWC level are reported elsewhere. 32 We used these data for calculating HWC costs and to derive the unit costs of treating diabetes or hypertension at HWCs (appendix pp [26][27].…”
Section: Sensitivity and Scenario Analysesmentioning
confidence: 99%
“…Investing adequately in health to create a single large purchaser would be the first step. 34 35 Second, decisions of the AB PM-JAY would need to be linked with HTA evidence. Conducive legislative measures to promote HTA would go a long way in realization of the aspirations of universal coverage and efficient health system for Indian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the high economic burden of NCDs in terms of out-of-pocket expenditure (OOPE) and catastrophic health expenditure for those utilising care from private sector providers [19][20][21][22]. Multiple studies conducted in different states of India have reported the input costs incurred by public facilities [23][24][25][26][27][28][29][30]. There is a very small set of studies reporting on the costs in the private sector but none of these studies have focused on NCD care [23,30].…”
Section: Introductionmentioning
confidence: 99%